BODY SCHEME: THEORETICAL CONSIDERATIONS (Fiep Bulletin - online, 2011)
The mental construction of the own body from subjective impressions (judgment values) and afferent input of multimodal (sigh, touch, proprioception) is called body awareness. We can identify two different aspects, but complementary in structuring of the body and its relationship with the environment and other bodies, corporal image and body scheme. It can be seen in the literature that studies published in this area refer to these terms as synonyms, but there are considerations consistent distinguishing these two concepts. Thus, the aim of this study is to clarify some conceptual issues relating to the body schema, presenting characteristics and relationships of this aspect of body awareness with the neurological organization of central nervous system.
Keywords: Body Image; Body Scheme; Central Nervous System